Pengaruh Struktur Modal, Profitabilitas, Ukuran Perusahaan dan Modal Intelektual Terhadap Nilai Perusahaan Pada Indeks LQ 45 Periode 2010-2017 - Roma Prima; Rangga Putra Ananto^2; Muhammad Rafi (Jurusan Akuntansi Politeknik Negeri Padang, 2018)
This study aims to examine the effect of capital structure, profitability, firm size and intellectual capital towards firm value. Capital structure is proxied by Debt to Equity Ratio (DER), profitability is proxied by Return On Assets (ROA), company size is proxied by Ln from total assets, intellectual capital is proxied by Value Added Intellectual Coefficient (VAIC) and company value is proxied by Price to Book Value (PBV). The data used in this study is secondary data obtained from the company's financial statements on the LQ 45 index listed on the Indonesia Stock Exchange for the period 2010-2017. The sampling technique was carried out using purposive sampling and obtained a sample of 15 companies. The data analysis technique used was multiple linear regression analysis using SPSS version 20. The results showed that the capital structure had no effect on the value of the company, profitability had an effect on the value of the company, the size of the company did not affect the value of the company and intellectual capital did not affect the value of the company.